INVESTIGATING THE INFLUENCE OF MUKTI ALI’S SCIENTIFIC-CUM-DOCTRINER ON AMIN ABDULLAH’S INTEGRATION-INTERCONNECTION IN ISLAMIC STUDIES - Adhika Alvianto; Muhammad Arif; Rosi Islamiyati; Muhammad Harkim Novridho (Al'Adalah, 2023)
Amin Abdullah's concepts of integration-interconnection and Mukti Ali's scientific-cum-doctriner have something in common. However, when developing his concept of integration-interconnection, Abdullah never quoted Ali's ideas, even though the relationship between the two thinkers and their thoughts was very close-as if the scientific-cum-doctriner concept was different from integration-interconnection. Abdullah prefers to cite the opinions of foreign thinkers, such as Ian G. Barbour, al-Jabiri, Nidhal Goessoum, and others when formulating integrations. Is it true that Abdullah tends to marginalize the conceptual role of Ali as his predecessor? Do the integration-interconnection and scientific-cum-doctor have nothing in common? This article investigates the influence and relationship of Ali's scientific-cum-doctriner thinking in Islamic studies in Indonesia. Abdullah admits that scientific-cum-doctriner is still at the level of method, not yet an approach, while integration-interconnection is already in the area of the approach. However, the two ideas have something in common. Both believed that one field of knowledge could not work independently, and both had the spirit to dialogue about the sciences, especially religious and other sciences.